Operational risk management : a complete guide to a successful operational risk framework - Girling, Philippa (Hoboken : Wiley, 2013)
BA best practices guide to all of the elements of an effective operational risk framework/b While many organizations know how important operational risks are, they still continue to struggle with the best ways to identify and manage them. Organizations of all sizes and in all industries need best practices for identifying and managing key operational risks, if they intend on exceling in today's dynamic environment./ iOperational Risk Management/i fills this need by providing both the new and experienced operational risk professional with all of the tools and best practices needed to implement a successful operational risk framework. It also provides real-life examples of successful methods and tools you can use while facing the cultural challenges that are prevalent in this field./ ulliContains informative post-mortems on some of the most notorious operational risk events of our time/liliExplores the future of operational risk in the current regulatory environment/liliWritten by a recognized global expert on operational risk/li/ul An effective operational risk framework is essential for today's organizations. This book will put you in a better position to develop one iand/i use it to identify, assess, control, and mitigate any potential risks of this nature.
Operational Risk Event DataInternal Loss Data or Internal Operational Risk Events; Why Collect Operational Risk Event Data?; Who Should Collect the Loss Data?; What Should Be Collected in the Loss Data Program?; Risk Event Categories; Internal Fraud; External Fraud; Employment Practices and Workplace Safety; Clients, Products, and Business Practices; Damage to Physical Assets; Business Disruption and System Failures; Execution, Delivery, and Process Management; Using the Basel Risk Categories; Minimum Loss Data Standards; Comprehensive; Threshold; Amount; Date; Description and Causes.
Includes bibliographical references and index.
Print version record.
Keywords: Risk management; Operational risk; Organizational change; Risk management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Risk management; Electronic books